Genus - Kongruenz und Klassifikation : Evidenzen aus dem Zweitspracherwerb des Deutschen. - Binanzer, Anja (DaZ-Forschung DaZ-For., 2017)
The DaZ-Forschung series presents current research on the acquisition of German as a second language and on education opportunities in the context of migration and multilingualism, in the form of monographs or anthologies. The volumes range from empirical and theory-forming studies through to application-oriented articles from the fields of second language acquisition, applied linguistics, education research, language didactics and language teaching. In thematic terms the series contains articles on sociolinguistic and psycholinguistic aspects, on the structure and dynamics of learner language.